A high-resolution temperature–salinity dataset observed by autonomous underwater vehicles for the evolution of mesoscale eddies and associated submesoscale processes in the South China Sea - C. Qiu; C. Qiu; Z. Du; Z. Du; H. Tang; H. Tang; Z. Yi; Z. Yi; J. Qiao; J. Qiao; D. Wang; D. Wang; et al. (Earth System Science Data)
Marginal seas are often characterized by dynamic mesoscale eddies (MEs), whose evolution plays a critical role in regulating global oceanic energy budgets, triggering submesoscale processes with strong vertical velocity, and facilitating biogeochemical transport. However, traditional observation methods, constrained by passive sampling modes, struggle to resolve the temporal evolution of MEs and associated submesoscale processes at kilometer-scale resolutions. Autonomous underwater vehicles (AUVs) and underwater gliders (UGs), operating in active sampling modes, provide spatio-temporal synchronized measurements of these highly dynamic features. Here, we present a 9-year (2014–2022) high-resolution temperature–salinity dataset collected by AUVs/UGs in the South China Sea (SCS), accessible via https://doi.org/10.57760/sciencedb.11996 (Qiu et al., 2024b). In total, the dataset comprises 11 cruise experiments that deployed 50 UGs and two AUVs, achieving spatial and temporal resolutions of < 7 km and < 7 h, respectively. This dataset offers unprecedented insights into ME evolution life stages, covering the zones of an eddy's birth, propagation, and dissipation. A total of 40 % of the data resolve submesoscale processes (< 1 km, < 4 h), capturing dynamic instabilities along and across frontal zones at eddy peripheries. This dataset has the potential to improve the forecast accuracy in physical and biogeochemistry numerical models. Much more aggressive field investigation programs will be promoted by the National Natural Science Foundation of China in the future.